ANALISIS FAKTOR PENGHAMBAT KONSEP RAMAH LINGKUNGAN DI OBJEK WISATA KUNCUNG MAS KABUPATEN KULONPROGO - Lastiani Warih Wulandari; Halim Ahmad (Pringgitan, 2021)
The tourist sector in Yogyakarta's Special Region (D.I.) Province is growing in a favorable way, as seen by the number of new tourism objects that are developing and continuing to appear. Yogyakarta's main draw is the combination of natural and cultural force. In places like Kuncung Mas, the concept of ecologically responsible tourism is attempting to serve as a vision for tourism growth. The tourism human resource component, on the other hand, becomes a roadblock in the development of eco-friendly tourism concepts. As a result, meticulous planning is required to ensure that the vision of an environmentally friendly concept does not deteriorate and emerge in damaging activities.Keywords: eco-friendly, kuncung mas, human resources